Enhancing oocyte in vitro maturation and quality by melatonin/bilirubin cationic nanoparticles: A promising strategy for assisted reproduction techniques - Haitao Xi; Lihui Huang; Lin Qiu; Shize Li; Yuqi Yan; Yang Ding; Yuhao Zhu; Fugen Wu; Xianbao Shi; Junzhao Zhao; Ruijie Chen; Qing Yao; et al. (Elsevier, 2024)
In assisted reproduction techniques, oocytes encounter elevated levels of reactive oxygen species (ROS) during in vitro maturation (IVM). Oxidative stress adversely affects oocyte quality, hampering their maturation, growth, and subsequent development. Thus, mitigating excessive ROS to safeguard less viable oocytes during IVM stands as a viable strategy. Numerous antioxidants have been explored for oocyte IVM, yielding considerable effects; however, several aspects, including solubility, stability, and safety, demand attention and resolution. In this study, we developed nanoparticles by self-assembling endogenous bilirubin and melatonin hormone coated with bilirubin-conjugated glycol chitosan (MB@GBn) to alleviate oxidative stress and enhance oocyte maturation. The optimized MB@GBn exhibited a uniform spherical shape, measuring 128 nm in particle size, with a PDI value of 0.1807 and a surface potential of +11.35 mV. The positively charged potential facilitated nanoparticle adherence to the oocyte surface through electrostatic interaction, allowing for functional action. In vitro studies demonstrated that MB@GB significantly enhanced the maturation of compromised oocytes. Further investigation revealed MB@GB's effectiveness in scavenging ROS, reducing intracellular calcium levels, and suppressing mitochondrial polarization. This study not only offers a novel perspective on nano drug delivery systems for biomedical applications but also presents an innovative strategy for enhancing oocyte IVM.